Transfer Free Energies of Test Proteins Into Crowded Protein Solutions Have Simple Dependence on Crowder Concentration - Nguemaha, Valery; Qin, Sanbo; Zhou, Huan-Xiang (Frontiers in Molecular Biosciences, 2019)
The effects of macromolecular crowding on the thermodynamic properties of test proteins are determined by the latter’s transfer free energies from a dilute solution to a crowded solution. The transfer free energies in turn are determined by effective protein-crowder interactions. When these interactions are modeled at the all-atom level, the transfer free energies may defy simple predictions. Here we investigated the dependence of the transfer free energy (Δμ) on crowder concentration. We represented both the test protein and the crowder proteins atomistically, and used a general interaction potential consisting of hard-core repulsion, nonpolar attraction, and solvent-screened electrostatic terms. The chemical potential was rigorously calculated by FMAP (Qin, S.; Zhou, H. X. J. Chem. Theory Comput. 2014, 10, 2824-2835), which entails expressing the protein-crowder interaction terms as correlation functions and evaluating them via fast Fourier transform (FFT). To high accuracy, the transfer free energy can be decomposed into an excluded-volume component (Δμe-v), arising from the hard-core repulsion, and a soft-attraction component (Δμs-a), arising from nonpolar and electrostatic interactions. The decomposition provides physical insight into crowding effects, in particular why such effects are very modest on protein folding stability. Further decomposition of Δμs-a into nonpolar and electrostatic components does not work, because these two types of interactions are highly correlated in contributing to Δμs-a. We found that Δμe-v fits well to the generalized fundamental measure theory (Qin, S.; Zhou, H. X. Phys. Rev. E 2010, 81, 031919), which accounts for atomic details of the test protein but approximates the crowder proteins as spherical particles. Most interestingly, Δμs-a has a nearly linear dependence on crowder concentration. The latter result can be understood within a perturbed virial expansion of Δμ (in powers of crowder concentration), with Δμe-v as reference. Whereas the second virial coefficient deviates strongly from that of the reference system, higher virial coefficients are close to their reference counterparts, thus leaving the linear term to make the dominant contribution to Δμs-a.